Inherently healthier design-current status and future directions in Malaysia - Nur Hasyimah Hanafi, 1989-, author; Mimi Haryani Hassim, supervisor; Fakulti Kejuruteraan Kimia (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2012)
Project Paper (Sarjana Muda Kejuruteran (Kimia)) - Universiti Teknologi Malaysia, 2012